2013
DOI: 10.1111/codi.12291
|View full text |Cite
|
Sign up to set email alerts
|

Persisting anorectal dysfunction after rectal cancer surgery

Abstract: Anorectal dysfunction is a frequent problem after management of rectal cancer with an impact on the well-being of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…This is in accordance with all other validation studies of the LARS score . It is already well documented that preoperative (chemo)radiotherapy results in an impaired QoL in patients with rectal cancer .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with all other validation studies of the LARS score . It is already well documented that preoperative (chemo)radiotherapy results in an impaired QoL in patients with rectal cancer .…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with all other validation studies of the LARS score [6][7][8][9]. It is already well documented that preoperative (chemo)radiotherapy results in an impaired QoL in patients with rectal cancer [18][19][20][21][22]. The Dutch version of the LARS score was also able to discriminate between types of surgery (PME vs TME), just as in the English and the consolidated international validations [6,9].…”
Section: Discussionsupporting
confidence: 88%
“…Sixty-seven percent of the patients in the TME-group had major LARS symptoms. These findings are in line with the literature showing a relatively high incidence of defecation problems after neoadjuvant CRT followed by TME, compared to TME only [40][41][42][43][44] . This can be explained by the pathophysiology of functional problems after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in one study, 45% reported occasional incontinence, while 16% reported complete incontinence . Other studies have reported liquid or solid fecal incontinence in 30% of patients and nocturnal incontinence in 53% of patients, indicating a high prevalence of bowel symptoms associated with sphincter‐sparing surgery for low rectal cancer . Poor bowel control reduces QOL primarily through embarrassment and social well being, rather than physical well being, and it can cause pain.…”
Section: Key Predictors Of Qolmentioning
confidence: 99%